2021
DOI: 10.1016/j.hrcr.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

How to leverage local impedance to guide effective ablation strategy: A case series

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In addition, ECI does not provide direct tissue feedback or real‐time localized tissue characteristics. Recently, a novel ablation catheter has been introduced into clinical use; this incorporates three equally spaced mini‐electrodes in the catheter tip and measures LI at the distal electrode of the catheter, without a reference skin electrode 9–13 . LI measurements taken with this catheter were found to well distinguish contact with healthy myocardium from contact with blood, and high‐voltage areas from low‐voltage areas; they were also able to detect significant differences in LI drop according to voltage level during ablation 9–13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, ECI does not provide direct tissue feedback or real‐time localized tissue characteristics. Recently, a novel ablation catheter has been introduced into clinical use; this incorporates three equally spaced mini‐electrodes in the catheter tip and measures LI at the distal electrode of the catheter, without a reference skin electrode 9–13 . LI measurements taken with this catheter were found to well distinguish contact with healthy myocardium from contact with blood, and high‐voltage areas from low‐voltage areas; they were also able to detect significant differences in LI drop according to voltage level during ablation 9–13 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel ablation catheter has been introduced into clinical use; this incorporates three equally spaced mini‐electrodes in the catheter tip and measures LI at the distal electrode of the catheter, without a reference skin electrode 9–13 . LI measurements taken with this catheter were found to well distinguish contact with healthy myocardium from contact with blood, and high‐voltage areas from low‐voltage areas; they were also able to detect significant differences in LI drop according to voltage level during ablation 9–13 . Most importantly, several studies showed that, in various types of arrhythmia, the absolute LI drops were significantly greater at effective ablation sites than ineffective sites 9,23 and the magnitude and time course of the LI drop during RF delivery was associated with effective lesion formation 10–12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using LI seems to be a safe method of providing data on tissue contact and characterization, and yields direct data for RF titration in order to obtain acute isolation, in agreement with previous findings. [10][11]27 At present, the use of catheters with contact-force sensors remains the gold standard for the RF ablation of AF. However, a structured approach based on LI information allowed us to achieve considerable clinical success.…”
Section: Ablation Guided By Local Impedance-sensing Capabilitymentioning
confidence: 99%